Enhanced visible-light degradation performance toward gaseous formaldehyde using oxygen vacancy-rich TiO2-x/TiO2 supported by natural diatomite. (1st July 2022) - Yuan, Fang; Yang, Renfeng; Li, Chunquan; Tan, Ye; Zhang, Xiangwei; Zheng, Shuilin; Sun, Zhiming
Abstract: Natural mineral-based composites with outstanding photocatalytic performance have attracted much attention because of their great potential applications in environmental remediation. Herein, we report a natural diatomite supported oxygen vacancy-rich TiO2-x -TiO2 homojunction (TOV -TD composite) photocatalyst for indoor gaseous formaldehyde (HCHO) purification. The designed composite exhibits superior sustainability and mineralization efficiency of HCHO under visible light illumination, which is attributed to the constructed high-efficient adsorption-photocatalysis collaborative system composed of TiO2, TiO2-x and diatomite. In addition, according to the variation of the CO2 concentration in real time, the calculated HCHO mineralization rate constant of TOV -TD-1:3 composite (optimal sample) is up to around 4.42 times that of bare TiO2-x (TOV ) and 1.74 times that of TiO2-x -TiO2 (TOV -T) composite, respectively. It is indicated that the introduction of the natural diatomite significantly promotes the content of oxygen vacancies in the composite and provides more adsorption-photocatalysis active centers. Moreover, the hydroxyl radicals ( OH) are proved to be the major active species for HCHO mineralization. This work provides a new composite for constructing adsorption-photocatalysis systems with enhanced visible-light properties for indoor HCHO removal. Highlights: A diatomite supported oxygen vacancy-rich TiO2-x -TiO2 homojunction was synthesized. The oxygen vacancy-rich structure improved photocatalytic abilities under visible light. An adsorption-catalysis collaborative system was constructed with in the composite. The introduction of the diatomite promotes the content of oxygen vacancies in the composite. The composite showed a lot of practical application potential for indoor HCHO removal.